Holding companies a structure for managing diversification (Philippine Management Review, 2009)
The holding company as an organization structure for managing diversification and growth of business operations in the Philippines and in other countries is discussed in this paper. It includes a discussion of: 1) the evolution of holding companies in the United States, South Korea, China and in the Philippines; 2) some advantages of forming holding companies in the Philippines and in other countries; 3) some disadvantages of forming holding companies; and 4) control issues arising from holding company-subsidiary relationships.